2022
DOI: 10.21608/tsnj.2022.253969
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bite-Sized Teaching Sessions on Parent’s Knowledge, Attitude, and Practice Regarding Febrile Seizures in Children

Abstract: Background: Febrile seizures are benign neurological disorders in children under the age of five and often make parents distressed and frightened leading to a relevant reduction in the quality of care. Aim: This study aimed to examine the effect of bite-sized teaching sessions on parents' knowledge, attitude, and practice regarding febrile seizures in children under five. Setting: The study was carried out over a period of six months from May to October 2021 in the Pediatric department at Governmental hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
3
0
1
Order By: Relevance
“…In conversation with parents during this study, it was found that mostly mothers were first to help the child, while fathers were the ones who called emergency medical services. In several studies, 100% of the respondents called for emergency medical services (22,23). The statement "I put a hard object in child's mouth" is also noteworthy as it was answered negatively by all but two respondents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In conversation with parents during this study, it was found that mostly mothers were first to help the child, while fathers were the ones who called emergency medical services. In several studies, 100% of the respondents called for emergency medical services (22,23). The statement "I put a hard object in child's mouth" is also noteworthy as it was answered negatively by all but two respondents.…”
Section: Discussionmentioning
confidence: 99%
“…In the study conducted in 2020 by Sayed, all parents placed their child on a soft and safe surface. Most respondents (86.7%) noticed the symptoms and followed the duration of the seizure, and 93.3% of them did not try to restrain the child during the seizure (22). During a seizure, the child should be restrained, i.e., involuntary movements of the extremities should be prevented to avoid selfharm and mitigate the risk of injury to others in the immediate surrounding.…”
Section: Discussionmentioning
confidence: 99%
“…Telah dilaporkan bahwa 25-35% anak seluruh wilayah dunia pernah dirawat di unit gawat darurat pediatrik dengan demam dan kejang demam (Kausar dkk., 2020). Hasil penelitian lain menyebutkan bahwa lebih dari 60% anak-anak pernah mengalami episode demam sebelum usia lima tahun di negara berkembang (Sayed, 2020). Prevalensi kejang demam pada anak di Indonesia dilaporkan mengalami peningkatan dari 3,5% pada tahun 2013 menjadi 5% pada tahun 2021.…”
Section: Pendahuluanunclassified
“…Also, parents' fear and stress can make child care difficult (8). Excessive fear and emotional damage of parents due to lack of awareness, causing excessive protection of the child, restrictions on the child's activities, sleep disorders, or other functional disorders (9,10). The reason for parents' fear and worry is largely because they do not know what is happening, how dangerous the seizure is, and what can be done about it (5).…”
Section: Introductionmentioning
confidence: 99%